Characterization and Effect of NaOH/ZnCl2 Chemical Activation on Nickel-Impregnated Activated Carbon for Biofuel - Azzahra, Balqis Ayu; Syam, Azhari Muhammad; Muhammad, Muhammad (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
The global energy crisis, driven by dwindling fossil fuel reserves and surging energy demand, necessitates a sustainable solution. Therefore, this research aimed to develop sugarcane molasses-based activated carbon as a support for nickel (Ni) catalysts to increase the efficiency of bio-oil conversion into biofuels. In these processes, activated carbon was produced by the dehydrogenation process of sugarcane molasses followed by the wet impregnation method using sodium hydroxide (NaOH) and zinc chloride (ZnCl2) activating agents. The analysis results showed that sugarcane molasses was effectively converted into activated carbon with optimal catalyst-loading properties. Based on the results of SEM-EDS and BET analysis, the activated carbon has a surface area with type III (IUPAC) indicating the presence of mesopores. Additionally, the use of the reflux process with Ni catalyst successfully converted coffee shell pyrolysis oil into hydrazine-based biofuel on the SMNa sample and heptadecane on the SMZn sample. The highest yield, 73.6% was found on SMZn. This research shows the great potential of sugarcane molasses as a raw material for the production of environmentally friendly biofuels while providing economic added value to biomass waste. These results will contribute to biomass energy conversion efforts in Indonesia.